Model Jaringan Syaraf Tiruan Dalam Pengenalan Penyakit Asam Lambung - Harbinder Singh; Budiman; Munika Murlia Giawa; Nia Zulfa Yanthi Simbolon (Jurnal Sains dan Teknologi, 2020)
The stomach has a very important role in the process of digestion of food, therefore we need to maintain its health in orderto avoid disturbances and its function can run normally. Acid reflux or what is known as GERD is one of the diseases commonlysuffered by many people, an unhealthy lifestyle is one of the triggers for the appearance of these symptoms. GERD is a pathologicalcondition resulting from reflux of gastric contents into the esophagus with various symptoms that arise due to esophagealinvolvement. Gastric disease is a common disease, with a prevalence of more than 50%. Neural Network (NN) is an accurate methodin helping doctors to analyze, model and understand complex clinical data in various medical fields, in research it is applied to theintroduction of gastric acid by applying the Nguyen Widrow algorithm to optimize training time in back-propagation networkarchitecture. . Based on the test results on the dataset, the Nguyen Widrow algorithm can only recognize 60% of the patient datasetsample with an average time of 0.049 seconds.